Protestantism in mainland Europe: new directions - MacCulloch, D (Renaissance Society of America, 2006)
Most stimulating - for this Anglophone historian, at least - has been the reintegration of religious history into mainstream social and political history generally, and also the heightened sense of an international movement embracing an entire continent and beyond. We no longer make artificial distinctions between the Reformation of the Atlantic Isles and those on the mainland; we can see more clearly what is local and what is part of an international phenomenon; and we can also appreciate the artificiality of considering Protestantism in isolation from reform movements in both the Pre-Reformation Western Church and Post-Tridentine Roman Catholicism. I commend the advantages of emancipating religious history from specific religious commitment. I also discuss the effect of the breaking down of barriers to travel and research in the wake of the 1989-90 revolutions in the recovery of our sense of the importance of Reformations in Eastern Europe, and also highlight our realization that a heritage of Southern European dissent shaped the heterodoxy that dissolved Reformation certainties.